Microbial Valorization of Lignin to Bioplastic by Genome-Reduced Pseudomonas putida - Zong, Qiu-Jin; Xu, Tao; Liu, He; Xu, Li; Zhang, Ren-Kuan; Li, Bing-Zhi; Liu, Zhi-Hua; Yuan, Ying-Jin (Frontiers in Microbiology, 2022)
As the most abundant natural aromatic resource, lignin valorization will contribute to a feasible biobased economy. Recently, biological lignin valorization has been advocated since ligninolytic microbes possess proficient funneling pathways of lignin to valuable products. In the present study, the potential to convert an actual lignin stream into polyhydroxyalkanoates (PHAs) had been evaluated using ligninolytic genome-reduced Pseudomonas putida. The results showed that the genome-reduced P. putida can grow well on an actual lignin stream to successfully yield a high PHA content and titer. The designed fermentation strategy almost eliminated the substrate effects of lignin on PHA accumulation. Employing a fed-batch strategy produced the comparable PHA contents and titers of 0.35 g/g dried cells and 1.4 g/L, respectively. The molecular mechanism analysis unveiled that P. putida consumed more small and hydrophilic lignin molecules to stimulate cell growth and PHA accumulation. Overall, the genome-reduced P. putida exhibited a superior capacity of lignin bioconversion and promote PHA accumulation, providing a promising route for sustainable lignin valorization.